Exploring Changes in Two Types of Self-Efficacy Following Participation in a Chronic Disease Self-Management Program - Graham, Kay; Smith, Matthew Lee; Hall, Jori N.; Emerson, Kerstin G.; Wilson, Mark G. (Frontiers in Public Health, 2016)
Chronic conditions and falls are related issues faced by many aging adults. Stanford’s Chronic Disease Self-Management Program (CDSMP) added brief fall-related content to the standardized 6-week workshop; however, no research had examined changes in Fall-related self-efficacy (SE) in response to CDSMP participation. This study explored relationships and changes in SE using the Self-Efficacy to Manage Chronic Disease Scale (SEMCD Scale) and the Fall Efficacy Scale (FallE Scale) in participants who successfully completed CDSMP workshops within a Southern state over a 10-month period. SE scale data were compared at baseline and post-intervention for 36 adults (mean age 74.5, SD ± 9.64). Principal component analysis (PCA), using oblimin rotation was completed at baseline and post-intervention for the individual scales and then for analysis combining both scales as a single scale. Each scale loaded under a single component for the PCA at both baseline and post-intervention. When both scales were entered as single meta-scale, the meta-scale split along two factors with no double loading. SEMCD and FallE Scale scores were significantly correlated at baseline and post-intervention, at least p<.05. A significant proportion of participants improved their scores on the FallE Scale post-intervention (p=.038). The magnitude of the change was also significant only for the FallE Scale (p=.043). The SEMCD Scale scores did not change significantly. Study findings from the exploratory PCA and significant correlations indicated that the SEMCD Scale and the FallE Scale measured two distinct but related types of SE. Though the scale scores were correlated at baseline and post-intervention, only the FallE Scale scores significantly differed post-intervention. Given this relationship and CDSMP’s recent addition of a10-minute fall prevention segment, further exploration of CDSMP’s possible influence on Fall-related SE would provide useful understanding for health promotion in aging adults.